Advances in Functional Metal‐Organic Frameworks Based On‐Demand Drug Delivery Systems for Tumor Therapeutics. Issue 8 (20th May 2021) - Nirosha Yalamandala, Bhanu; Shen, Wei‐Ting; Min, Sheng‐Hao; Chiang, Wen‐Hsuan; Chang, Shing‐Jyh; Hu, Shang‐Hsiu
Abstract : Dual on‐demand delivery of therapeutic cargos and energy by transporters can latently mitigate side effects and provide the unique aspects required for precision medicine. To achieve this goal, metal‐organic frameworks (MOFs), hybrid materials constructed from metal ions and polydentate organic linkers, have attracted attention for controlled drug release and energy delivery in tumors. With appropriate characteristics such as tunable pore size, high surface area, and tailorable composition, therapeutic agents (drug molecules or responsive agents) can be effectively encapsulated in MOFs. Based on their intrinsic properties, many physically or chemically responsive agents are able to achieve precise on‐demand drug release and energy generation (thermal or dynamic therapy) using MOFs (as energy absorbers). Herein, the results obtained with various stimuli‐responsive MOFs (including materials from the Institute Lavoisier [MIL], zeolitic imidazolate frameworks [ZIFs], MOFs from the University of Oslo [UiO], and other MOFs) used for tumor suppression are summarized. Furthermore, with the appropriate stimulus, catalytic therapy (caused by the Fenton reaction induced by MOFs) can be provided via the utilization of existing high levels of H2 O2 in cancer cells, which potentially elicits immune responses. In addition, the issues impeding clinical translation are also discussed, including the need to overcome tumor heterogeneity and to recognize the innate immune system and possible effects. As the references reveal, additional comprehensive strategies and studies are needed to enable broad applications and potent translational developments. Abstract : Metal‐organic frameworks (MOFs) possessing various physical‐ or chemical‐responsive properties achieve the precisely on‐demand drug release and energy generation (thermal or dynamic therapy) for cancer therapy.